(untitled) (Journal of Kidney Cancer, 2023)
The utility of partial nephrectomy (PN) in locally advanced, stage T3 renal cell carcinoma (RCC) is controversial. This retrospective study aimed to review the oncological and functional outcomes of patients with T3a RCC who underwent PN. We included all patients with pT3a stage RCC undergoing either open, laparoscopic, or robotic PN at our center between January 2015 and 2023. A Wilcoxon rank sum test was utilized to compare nephrectomy types (radical nephrectomy [RN] vs PN). Survival analysis was conducted using Kaplan–Meier plots and a log-rank test. P-value < 0.05 indicated statistical significance. There were no significant differences in demographic characteristics between the RN and PN groups, except age (53.0 vs 6.5, respectively; P = 0.012) and body mass index (28.7 vs 34.3, respectively; P = 0.020). Furthermore, there were also no significant differences in the rates of local recurrence (P = 0.597), metastatic progression (P = 0.129), and chemotherapy use (P = 0.367) between nephrectomy types. Patient survival did not differ significantly based on the type of nephrectomy (log-rank P-value = 0.852). Together, our findings indicated that PN and RN yield near-equivalent oncological outcomes in terms of local recurrence, metastasis, and overall survival rates among pT3a RCC patients during a nearly 3-year follow-up period.